2020
DOI: 10.1192/j.eurpsy.2020.103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interactions between variation in dopaminergic genes, traumatic life events, and anomalous self-experiences on psychosis proneness: Results from a cross-sectional study in a nonclinical sample

Abstract: Effects of interactions between variation in dopaminergic genes, traumatic life events and anomalous self-experiences on psychosis proneness: Results from a cross-sectional study in a non-clinical sample

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 66 publications
2
8
0
Order By: Relevance
“…It consists of nine items assessing perceptual alterations, five items to investigate delusional ideation, paranoia and unusual thought, and two items to screen for attenuated negative symptoms. In our study, we used the Polish version of the questionnaire that was prepared using a back-translation procedure and was used in our several previous studies [ 6 , 12 , 18 ]. The original PQ-16 consists of two scales, where the first one records whether PLEs are “present” or “non-present”, and the second one assesses the level of distress associated with PLEs on a four-point Likert-like scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists of nine items assessing perceptual alterations, five items to investigate delusional ideation, paranoia and unusual thought, and two items to screen for attenuated negative symptoms. In our study, we used the Polish version of the questionnaire that was prepared using a back-translation procedure and was used in our several previous studies [ 6 , 12 , 18 ]. The original PQ-16 consists of two scales, where the first one records whether PLEs are “present” or “non-present”, and the second one assesses the level of distress associated with PLEs on a four-point Likert-like scale.…”
Section: Methodsmentioning
confidence: 99%
“…Several models have been proposed so far in the development of PLEs, showing the association of genetic background [ 6 , 7 ], cannabis use [ 8 ], cognitive biases [ 9 , 10 ], self-disturbances [ 11 ], insecure attachment style [ 12 ] and early traumatic adversities [ 13 ] with the higher risk of PLEs [ 14 ]. Moreover, it has been reported that childhood trauma and PLEs are associated with increased suicidal risk in young adults [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such interaction can be defined as a genetic modulation of the sensitivity to environmental factors and/or environmental control of the gene expression (Kendler and Eaves, 1986). Numerous studies supported this hypothesis (Collip et al, 2013;Frydecka et al, 2020;Pries et al, 2020a), and particularly one from Caspi et al (2005), in which a significant interaction between cannabis use in adolescence and the genetic variant Val 158 Met in the Catechol-O-Methyltransferase (COMT, which metabolises dopamine) gene was found. In this study, in comparison to Val/Val genotype, Met/Met and Met/Val genotypes had a protective effect against the risk of psychotic symptoms and disorders among cannabis users (in the group of subjects without cannabis use, the rates of psychotic symptoms and disorders were similar according to the different genotypes).…”
Section: Introductionmentioning
confidence: 94%
“…In addition to increasing the risk for psychosis by GxE interactions, the PRS-SZ has also been associated with a greater risk of exposure to environmental risk factors for psychosis (Pingault et al, 2018). For instance, several studies have reported associations between the PRS-SZ and cannabis use (Gage et al, 2017;Pasman et al, 2018) or between the PRS-SZ and urbanicity (Colodro-Conde et al, 2018;Paksarian et al, 2018;Maxwell et al, 2021) or the level of neighbourhood deprivation and social fragmentation at birth (Solmi et al, 2020), challenging the traditional gene v. environment dichotomy. However, these observations could not explain the strength of the associations between cannabis use or urbanicity and the risk of psychotic disorders (Vassos et al, 2012;Di Forti et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, our knowledge is still incomplete. The newest studies in the field have suggested the interaction between genetic, environmental factors, and cognitive biases in predicting the risk of psychosis [e.g., (15)]. Hence, further integration is warranted to gather new insights that may apply to clinical practice.…”
Section: Editorial On the Research Topic The Relationship Between Cognitive Biases And Psychosis: Searching For Mechanismsmentioning
confidence: 99%